The Discourse of Women’s Religious Leadership in Hinduism and Buddhism - Afifur Rochman Sya'rani (Religi: Jurnal Studi Agama-agama, 2022)
In Hinduism and Buddhism, religious leadership is commonly associated with men. However, historical evidence shows that women had become religious leaders, though their appearance was marginal and not publicly visible. With the rise of modernity, the existence of female religious leadership has begun to be publicly recognized and visible. Though there have been patriarchal elements and practices in Hinduism and Buddhism, the two religions have provided spaces and opportunities for women's religious leadership. This article, thus, seeks to comparatively examine the discourse of women’s religious leadership in Hinduism and Buddhism. In what ways and contexts can Hindu and Buddhist women be religious leaders? What constitutes women's religious leadership in the two religions? This article argues that both Hindu and Buddhist traditions are ambivalent about female religious leadership. While the religious leadership of Hinduism is charismatic, non-institutionalized, and highly dependent on public recognition, that of Buddhism, by contrast, is institutionalized and significantly determined by the established rules of Buddhist monastic institutions (Sangha). The divergent models of religious leadership suggest different ways in which female religious leaders are recognized.